Evaluasi Usability Sistem Informasi TSES (Thursina Smart Education System) menggunakan Usability Testing dan System Usability Scale - Irfan Nuril Faza; Satrio Hadi Wijoyo; Intan Sartika Eris Maghfiroh (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
TSES (Thursina Smart Education System) is an academic service information system owned by the Thursina IIBS Malang Islamic boarding school to facilitate the learning process. Thursina IIBS Malang Islamic boarding school is one of the modern Islamic boarding schools in Malang, where this Islamic boarding school follows and implements technological developments that occur, one of which is through the TSES system (Thursina Smart Education System). Since the initial release, in 2019, there has been no research on usability evaluation of TSES (Thursina Smart Education System). This condition allows usability problems that are not yet known. Given the function of TSES as a support for learning activities at the Thursina IIBS Malang Islamic boarding school, evaluation is needed to analyze the level of usability and measure the success of using information systems. The purpose of this research is to evaluate the performance and problems of the TSES learning system. The expected results of this study are to be able to provide recommendations for the development of the TSES Thursina IIBS Malang. The redesign method used is Human Centered design with reference to the HHS Usability Guidelines, as well as the System Usability Scale (SUS) and usability testing evaluation method. Improvements based on the results of interviews and usability testing in the form of adding a forgotten password feature, a password change feature, a search feature, an excel import feature, changes to the existing navigation system and content layout. The evaluation results show that the average value of the learnability aspect of teachers and students is 96%, the average efficiency aspect of teachers and students is 94.5%, the average aspect of memorability of teachers and students is 35.5 clicks with 112.4 seconds, the average -the average error aspect of teachers and students is 2% and the results obtained for the satisfaction aspect are 84.13. Based on the research results, it was found that the solution design developed based on the evaluation results of the TSES was well received.